The EDUKASI BULLIYING TERHADAP SISWA SDN 02 KADUNGORA GARUT - Putri Syifa Nur Fauziah; Husna Mardhiyah; Oriza Purna Setya; Muhammad Yasir Jihad Irsam; Aidah Hayatun Nufus (Makkareso: Riset Pengabdian Masyarakat, 2026)
This community service project aimed to address the issue of bullying among elementary school students through an educational outreach program at SDN 2 Kadungora, Garut Regency. Bullying, which can manifest verbally, physically, socially, and online, has long term negative impacts on children’s psychological well being, academic performance, and social development. The program sought to enhance students’ awareness of bullying, equip teachers and homeroom teachers with preventive strategies, and engage parents in fostering a safe learning environment. The project was conducted using interactive education methods, including presentations, video screenings, role-playing, and group discussions, complemented by commitments from students to create a bullying-free environment. The activities involved 5th- and 6th-grade students, selected due to their developmental stage, which is highly vulnerable to bullying behaviors. Evaluation showed increased student engagement, improved understanding of bullying forms and consequences, and stronger teacher, student, parent collaboration in prevention efforts. The success of this program was reflected in students’ willingness to report bullying, improved empathy, and a visible reduction of bullying behavior in the classroom. This initiative demonstrates that participatory, character-based education is an effective approach for creating a safe and inclusive school culture, and it highlights the importance of early intervention in children’s character development